DETERMINING OPERATIONAL EFFICIENCY IN AQUACULTURE ENTERPRISE TO BOOST FISH PRODUCTION FOR IMPROVED FOOD SECURITY IN SOUTHWEST, NIGERIA - Olaniran Anthony THOMPSON; Taiwo Timothy AMOS; Lawrence Olusola OPARINDE; Olajumoke Olamiposi OMOSOWONE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The mainintent of the research is to: (i) establish the cost-effectiveness of aquaculture fish farmers in the study area; (ii) evaluate how efficient the fish farmers are in theiruse of resources; (iii) ascertain the variables inducing the efficient use of resources; (iv) and establish the majorlimitations encountered by the owner and manager of fish farm enterprisein the area of study. Multistage samplingprocedure was used to select 180 aquaculture fish farmers in the area of study. Some analytical methods such as net profit margin ratioand efficiency model were used to investigate the collected data on the field.The result revealed that the average age of the respondents was 35.8 years. Their average years of experience in fish farming enterprise was 12.9 years. The net profit margin ratio was 21.96%, the operating expense ratio was 72.76% and the fixed cost ratio was 5.29%. The study further shows thatgender, educational level, aquaculture fish farming experience, pond size, association/cooperative membership and access to extension agents had positive value and significantly influence the aquaculture fish farmer’s operational efficiency in the area of study. The research recommends that aquaculture fish farmers should be sensitized on the need to acquire more education and make use of the extension agents in their aquaculture fish farming.